Drivers of change: how the food system of the Lisbon Metropolitan Area is being shaped by activities, initiatives and citizens needs towards a sustainable transition - Marat-Mendes, T. (2021)
Food has always been an urban issue. The role of cities in building more sustainable food systems is already recognized and related to other urban domains, such as transport, health, land use planning for agriculture and multifunctional areas, community development, employment generation and waste management. The implications of these on urban planning and practice are however less evident. A proper spatialization of the food system and of its metabolic flows is missing, inhibiting their necessary readings for urban design. This paper addresses this gap. After introducing the concept of food system and discussing its spatial components – production, transformation, distribution, commercialization/consumption and waste management – we expose how a set of food-related activities and initiatives are shaping the Lisbon Metropolitan Area. The socio-ecological metabolic flows established by these operations on the ground and their sustainability impacts are established, based on the analysis of five municipalities: Lisbon, Oeiras, Alcochete, Palmela and Montijo. The results reveal how food is already an opportunity for the creation of jobs, healthy food markets and the promotion of land productivity, in particular on a micro scale. The paper recognizes the importance of localized food systems and their particular metabolic flows, capable of boosting opportunities to overcome physical and social obstacles and to increase the possibilities for urban planning to target the urban food system on a wider scale. Finally, it concludes that the overall food system of a metropolitan area is more than the sum of the several food systems operating in that same region